Mesenchymal Stem Cell Therapy for Treating the Underlying Causes of Diabetes Mellitus and Its Consequences - Esquivel, Diana; Mishra, Rangnath; Srivastava, Anand (Current Stem Cell Research & Therapy, 2024)
Diabetes mellitus (DM) is a multifaceted pathological condition, which at present is being considered an epidemic disease keeping the rampant rate of its increase in almost all population groups of the world in consideration. Out of the two types of DM described, T1D is characterized as an autoimmune condition that leads to the destruction of pancreatic β-cells by macrophages and T-cells, thereby, adversely affecting the production of insulin. On the other hand, T2D, often caused by insulin resistance, is commonly related to unhealthy habits, and therefore, it can be prevented in most cases. In both of the conditions, high levels of proinflammatory cytokines like IL-6, TNF-α, and INF-ϒ, lead to chronic inflammation, and elevated oxidative stress resulting in apoptosis and destruction of tissues. Although several treatments are available to treat the symptoms, the underlying causes are not well addressed. One of the most promising approaches to tackle the ill effects and the primary causes of DM is mesenchymal stem cell (MSC) therapy. The use of MSC therapy, because of the immunomodulatory and regenerative properties recorded in this type of cells in a number of experiments carried out in animal models and clinical trials of the disease, has reported positive outcomes. This review covers the principal mechanisms of action induced during MSC therapy in reference to the described pathophysiological pathways of both T1D and T2D. In addition, how this therapeutic intervention can counteract the ill effects of this condition leading to the promotion of tissue regeneration has been covered.
Keywords: Diabetes mellitus